Heritability of body mass index and physical activity in Ukrainian adolescents - E.M. Omelchenko; O.T. Yelizarova; N.S. Polka; O.O. Polka; S.V. Hozak (Medičnì Perspektivi, 2022)
The article analyzed the lifestyle and physical development of Ukrainian adolescents and their parents and estimated the familial aggregation and heritability of body mass index and physical activity. 408 nuclear families were examined (1216 people with complete information).  Anthropometric measures such as weight, height were measured following standardized procedures of WHO. Questionnaires were used to estimate the levels of physical activity. The method of genetic epidemiology research was used to explore heritability (h2) and family aggregation (ρ). Analysis was performed using the software product S.A.G.E. The study showed that 12.0±1.6% of children were overweight or obese, 6.4±1.2% were underweight and 81.6±1.9% with normal weight. It was found that among adolescents aged 12-15 years, 17.5±3.1% of boys and 32.7±2.9% of girls were physically inactive. Body mass index values higher than 25.0 kg/m2 were found in 34.3±2.4 mothers and in 70.6±2.3% of fathers. The proportion of physically inactive persons was 45.7±2.5% among mothers and 51.1±2.7% among fathers. Heritability values were significant for both body mass index (h2 =0.41±0.09; p<0.001) and physical activity (h2 =0.23±0.07; p<0.001). Significant familial correlations were obtained between parents-offspring for physical activity (ρ=0.20±0.04; p<0.001) and body mass index (ρ=0.25±0.03; p<0.001). The study estimated that the familial correlations for physical activity between mother-son and mother-daughter pairs were higher than in father-son and father-daughter pairs. The highest is the mother-daughter aggregation (ρ = 0.29 ± 0.06; p <0.001), the lowest is the father-son (ρ=0.19±0.08; p<0.05) by body mass index. As physical inactivity and overweight increase the risk of non-communicable diseases development, the data obtained should be taken into account while planning preventive measures.